2001
DOI: 10.1108/eum0000000005856
|View full text |Cite
|
Sign up to set email alerts
|

Some psychosocial problems of police officers in Lithuania

Abstract: Stress plays an important role in human life. Under normal conditions it has a favorable influence. However, constant pathological stress can be harmful. The results can be depression, leading sometimes to alcohol and/or drug abuse, or suicide. Some specific groups of society are affected by stress more frequently and more severely. One of these groups is the police. This article aims to identify key psychosocial problems which police officers of Lithuania are encountering in an independent post‐communist stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…Conversely, in a quasi‐military organization in which wrong decisions can have serious judicial consequences for the individual police officers, defective leadership, blurred chains of command, role conflicts, and lack of trust among fellow officers, form stressful combinations (see, e.g. Violanti, 1997; Kop et al , 1999; Zukauskas et al , 2001; Liberman et al , 2002; Toch, 2002; Buker and Wiecko, 2007; Gershon et al , 2009; Shane, 2010).…”
Section: Police Stressorsmentioning
confidence: 99%
“…Conversely, in a quasi‐military organization in which wrong decisions can have serious judicial consequences for the individual police officers, defective leadership, blurred chains of command, role conflicts, and lack of trust among fellow officers, form stressful combinations (see, e.g. Violanti, 1997; Kop et al , 1999; Zukauskas et al , 2001; Liberman et al , 2002; Toch, 2002; Buker and Wiecko, 2007; Gershon et al , 2009; Shane, 2010).…”
Section: Police Stressorsmentioning
confidence: 99%
“…Range of drug addiction is indeed much smaller than from alcohol, but nevertheless it is a phenomenon that can not be underestimated [25]. It should be noted that the problem of substance abuse among police officers never goes away, it never disappears stress of the job.…”
Section: The Causes Of Alcoholism By Police Officersmentioning
confidence: 97%
“…Having analyzed the media education theories developed by media educators from different countries Irina Fateeva concluded that "to derive a media education theory from communication theories is not only unreasonable but also destructive since that initially causes conceptual disunity of teachers and their pupils intensified by moral and ethical problems: after failing to reach a consensus in the dispute the teachers are apt to impose their arguable views on the audience" [Fateeva, 2007, p. [25][26].…”
Section: Alcohol Abuse By Policementioning
confidence: 99%
“…Research had shown that police work can be considered a profession with stress (Anshel, Robertson, & Caputi, 1997;Reese, 1986). This stress could cause a number of negative effects for police officers, including lowered productivity, lowered organizational commitment, and serious health problems (Band & Manuele, 1999;Golembiewski & Kim, 1991;Hackett & Violanti, 2003;Jaramillo, Nixon, & Sams, 2004;Richmond, Wodak, Kehoe, & Heather, 1998;Storch & Panzarella, 1996;Waters & Ussery, 2007;Zukauskas, Dapsys, Jasmontatite, & Susinskas, 2001).…”
Section: Work Stressmentioning
confidence: 97%